THE ROLE OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE MODERN DIGITAL ECONOMY - Madrakhimov Kakhramon Egamberganovich (American Journals Publishing, 2026)
This article explores the influence of artificial intelligence technologies on managerial decision-making processes within the digital economy from scientific, theoretical, and applied viewpoints. The research focuses on the adoption of artificial intelligence across various economic sectors, its functional significance in public governance and business operations, as well as its contribution to improving economic performance. The level of artificial intelligence implementation is examined through the case of Uzbekistan, highlighting its strategic role in ensuring the sustainable development of the digital economy. The findings indicate that the consistent application of artificial intelligence in management decision-making enhances economic efficiency and supports institutional advancement.
Keywords: Artificial intelligence, digital economy, management decisions, digital transformation, information security, public administration, innovation, economic efficiency, application of artificial intelligence, technologies.